Factors, barriers and adherence of nurses to patient education in public hospitals of Lanao del Sur, Philippines - Omar, Naseha M.; Mala, Naima D.; Bangcola, Ashley A. (Universitas Airlangga, 2024)
Introduction: Patient education is a core responsibility in nursing, vital for improving patient understanding and active participation in their healthcare decisions. There are various factors that impact nurses' ability to provide patient education, but little is known about how these factors influence adherence in public hospitals, particularly in resource-limited settings. This study investigates nurses' adherence to patient education protocols in Lanao del Sur, Philippines, while evaluating facilitating factors and barriers. Methods: This study employed a quantitative, descriptive, cross-sectional correlational research design. Seventy-six nurses from two public district hospitals participated. Data were gathered through surveys on demographics, adherence to patient education, facilitators, and barriers. Correlation analyses, including Pearson’s correlation and Spearman’s rho, assessed relationships between variables, with Cramer’s V used for categorical data. Statistical significance was set at α = 0.05. Results: Most participants were married females aged 31-40, with incomes of 10,000-39,000 PHP, college-educated, and assigned to wards, with 3 months to 3 years of tenure. Nurses acknowledged the importance of patient education and identified 14 barriers. Adherence to patient education showed negative correlations with age, income, educational attainment, and tenure, but positive correlations with gender, marital status, and area of assignment. Facilitating factors positively correlated with adherence, as did barriers. Conclusions: Identifying factors affecting nurses' adherence to patient education is vital for improving these practices. Findings will support the Nursing Patient Education Development Program, enhancing patient education in Lanao del Sur's public hospitals.